Extracellular exosome signature links hypertension and Alzheimer’s disease - Joakim A. Bastrup; Jonas Folke; Sanne S. Kaalund; Michel Rasmussen; Susana Aznar; Thomas Jepps (GeroScience, 2026)
Untreated hypertension is a risk factor for late-onset Alzheimer’s disease (AD); however, this association is not well understood. The aim of this study was to reveal protein signatures that bridge the pathophysiological changes in hypertension to AD. Using untargeted proteomics, we analyzed brain samples from aged (30- and 40-week-old) spontaneously hypertensive rats (SHRs, n = 12), and age-matched normotensive Wistar Kyoto (WKY, n = 8) controls, and human AD patients (Braak stages 4–6) ( n = 30), cerebral amyloid angiopathy (CAA) ( n = 5), non-demented controls (Braak stages 0–3) ( n = 37). Differential expression and pathway analyses in SHRs highlighted the ‘extracellular exosome’ pathway. This pathway also showed significant associations to differentially expressed proteins in AD and CAA patients. Comparison between species identified 24 proteins in SHRs and AD, whose trajectory pattern over the progression of hypertension, aligned with those observed during AD Braak stage progression, compared to respective controls. The proteins were similarly associated with extracellular exosomes. Immunostaining and spatial proteomics support vesicle accumulation and dysregulated exosome protein signatures in the cerebrovasculature of both SHR and AD brains. Additionally, the extracellular exosome pathway-association was not identified in a traditional model of familial AD (5xFAD). Our findings demonstrate cross-species translatability between AD and the SHR and provide novel mechanistic insights into a shared dysregulation of cerebral artery-associated exosomes. Graphical Abstract

Database development and LIBS calibration for the LIBS-Raman Sensor for planetary exploration - E.R. Sawyers; G. Lopez-Reyes; A. Barlow; M. Veneranda; E.A. Lymer; E.A. Cloutis; J. Manrique; B. Barrios; S. Julve; J. Freemantle; M. Aznar; M.G. Daly; et al. (Icarus, 2025)

Anisakis spp. as indicators of latitudinal movements of short‐finned pilot whales, Globicephala macrorhynchus , in the Northeast Atlantic - Claudia Pons‐Bordas; Rachel V. Pool; Sofía Ten; José A. Armenteros‐Santos; Ana Balseiro; Manena Fayos; F. Javier Aznar (Marine Mammal Science, 2025)
In the Northeast Atlantic, it is unclear whether short‐finned pilot whales, Globicephala macrorhynchus (SFPWs), are transient or resident above 40°N. We used Anisakis spp. to identify the latitudes recently visited by a SFPW pod stranded in NW Spain (43°N) in 2020. Analysis of cox2 gene in 30 nematodes from 6 SFPWs revealed the presence of A. simplex sensu stricto (s.s.) (93.3%) and A. pegreffii (6.7%). Morphological analysis of 972 nematodes corroborated species molecular identification and relative proportions; in males ( n = 66), the estimated proportions of A. simplex s.s. and A. pegreffii were 86.4% and 13.6%, respectively. These percentages resembled those reported in fish/cetaceans above 40°N, and L4 larvae or adults of A. typica (a tropical‐temperate species found in SFPWs up to 38°N–39°N) were not detected. Population structure of A. simplex s.s. + A. pegreffii in SFPWs suggested a continuous recruitment of nematodes starting at least 3 weeks before stranding. We interpret that either the SFPW pod was within the range of the species (perhaps as a recent northern shift) or represented a vagrant group that visited waters off Northwest Spain for a protracted period. Future analysis on nematode assemblages could shed light on movements and climate‐driven shifts in cetacean distribution.

The epibiont Xenobalanus globicipitis indicates differences in swimming kinematics among cetaceans - Sofía Ten; Francesca Fusar Poli; Kenji Konishi; Luis A. Pastene; Vidal Martín; Juan Antonio Raga; Francisco Javier Aznar (Marine Biology, 2025)
Most research on cetacean swimming has been conducted on captive dolphins due to limited accessibility to wild cetaceans. Epibiotic barnacles have been used as indirect evidence of cetacean hydrodynamics, given their lifelong association with cetaceans and dependence on water flow. Previous studies suggested that the spatial distribution of the barnacle Xenobalanus globicipitis on the tail flukes of striped dolphins (i.e., higher load in the center and dorsal side) sheds light on dolphin hydrodynamics. The present study investigates whether these spatial patterns are shared among 13 cetacean species: 1 species of baleen whale ( N =33), 3 beaked whales ( N =11), and delphinids: 3 globicephalines ( N =21) and 6 smaller dolphins ( N =118). We found higher barnacle densities on the dorsal side of the flukes of delphinids, particularly in the smaller species (mostly subfamily Delphininae); whereas both fluke sides of the whales were equally colonized. The center of the flukes was generally a preferred settlement location for X. globicipitis , although it became less predictable in the ventral side of dolphins. Our findings conform to evidence on cetacean morphokinematics: while large odontocetes and whales have greater mobility in their torso during swimming, dolphins rely mostly on asymmetric fluke oscillation, likely favoring a set of more favorable conditions for barnacle settlement on the dorsal fluke side of dolphins (i.e., higher cyprid advection and lower shear stress). Also, the interaction of the dorsal fin vortices with the flow at the flukes could be more pronounced in dolphins. An additional effect of dolphin aerial behavior cannot be ruled out. This study provides novel indirect evidence on cetacean swimming performance, highlighting possible nuances between ecomorphological groups, and underlines that epibionts are a cost-effective tool for studying wild cetaceans.

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

Fine‐scale distribution of the lungworm Halocercus delphini in the lungs of the striped dolphin, Stenella coeruleoalba : implications about migration pathways and functional significance - Rachel V. Pool; Neus Pons‐García; Francesco Consoli; Miguel Rivero; Cristiano Bombardi; Juan A. Raga; Francisco J. Aznar (Marine Mammal Science, 2024)
Despite their high pathogenicity, limited knowledge is available on intrahost migration pathways and microhabitat distribution of pseudaliid lungworms. In this study, the distribution of Halocercus delphini in the lungs of the striped dolphin, Stenella coeruleoalba , was analyzed on three scales: between the right and left lungs, within the lungs, and between worm clusters. Evidence of a relationship between the distribution of H. delphini and the perfusion of the lungs of S. coeruleoalba is provided by the consistent correlation of these two factors, both on a longitudinal scale and by the difference in parasite burden between the left and right lung. This relationship, when coupled with the nested pattern of colonization, suggests that this species, like many other metastrongyloids, migrates to the lungs via the circulatory system. Additionally, the concentration of lungworms around the major airways could be a further reflection of the well‐perfused nature of these passageways. Equally, this distribution could be a strategy to minimize the distance that larvae must travel to exit the lungs via the trachea, as do most other metastrongyloids. On a more localized scale, the tendency of H. delphini to form distinct heterosexual clusters even at low infection intensities indicates active mate‐seeking behavior for reproduction.

Initial evaluation of USP apparatus 4 for measuring dissolution profile of man-made vitreous fibers - J.W. Hoffman; D.V. Okhrimenko; E. Chaudan; Q. Herault; N. Drnovsek; E. Pezennec; A. Aznar; N. Mascaraque; S. Haddouchi; M. Lecluse; A.A. Badissi; J. de Cruz; et al. (Toxicology Letters, 2023)

Raman-IR spectroscopic, and XRD analysis of selected samples from Fogo Island, Cabo Verde: Implications for ancient Martian volcanology - M. Aznar; A. Sanz-Arranz; S. Shkolyar; E.R. Sawyers; M. Konstantinidis; G. Lopez-Reyes; M. Veneranda; E.A. Lymer; J.R. Freemantle; M.G. Daly; E.A. Cloutis; F. Rull-Perez; et al. (Advances in Space Research, 2023)

H﻿ow on Earth did that get there? Natural and human vectors of aquatic macrophyte global distribution - Tatiana Lobato‑de Magalhães; Kevin Murphy; Andrey Efremov; Thomas A. Davidson; Eugenio Molina-Navarro; Kevin A. Wood; Julissa Tapia-Grimaldo; Deborah Hofstra; Hui Fu; Ileana Ortegón-Aznar (Hydrobiologia, 2023)

Epibiotic Fauna on Cetaceans Worldwide: A Systematic Review of Records and Indicator Potential - S. Ten; J. A. Raga; F. J. Aznar (Frontiers in Marine Science, 2022)
Each individual cetacean is an ecosystem itself, potentially harboring a great variety of animals that travel with it. Despite being often despised or overlooked, many of these epizoites have been proven to be suitable bio-indicators of their cetacean hosts, informing on health status, social interactions, migration patterns, population structure or phylogeography. Moreover, epizoites are advantageous over internal parasites in that many of them can be detected by direct observation (e.g., boat surveys), thus no capture or dissection of cetaceans are necessary. Previous reviews of epizoites of cetaceans have focused on specific geographical areas, cetacean species or epibiotic taxa, but fall short to include the increasing number of records and scientific findings about these animals. Here we present an updated review of all records of associations between cetaceans and their epibiotic fauna (i.e., commensals, ecto- or mesoparasites, and mutualists). We gathered nearly 500 publications and found a total of 58 facultative or obligate epibiotic taxa from 11 orders of arthropods, vertebrates, cnidarians, and a nematode that are associated to the external surface of 66 cetacean species around the globe. We also provide information on the use as an indicator species in the literature, if any, and about other relevant traits, such as geographic range, host specificity, genetic data, and life-cycle. We encourage researchers, not only to provide quantitative data (i.e., prevalence, abundance) on the epizoites they find on cetaceans, but also to inform on their absence. The inferences drawn from epizoites can greatly benefit conservation plans of both cetaceans and their epizoites.

Pseudidiomarina piscicola sp. nov., isolated from cultured European seabass, Dicenthrarchus labrax - M. Carmen Macián; Teresa Lucena; David R. Arahal; María A. Ruvira; Rosa Aznar; María J. Pujalte (Archives of Microbiology, 2021)
Strain CECT 9734 T , a Gram-negative, aerobic, chemoorganotrophic bacterium, motile by polar flagella, was isolated from cultured European seabass, Dicenthrarchus labrax, in Spain. It grows from 5 to 42 ºC, 6–9 pH and 1–12% total salinity. Major cellular fatty acids are C 15:0 iso, summed feature 9 (C 17:1 iso w9c /C 16:0 10-methyl) and C 17:0 iso. The genome size is 2.5 Mbp and G + C content is 49.5 mol%. Comparative analysis of the 16S rRNA gene sequence shows that the strain is a member of Pseudidiomarina , with highest similarities with Pseudidiomarina halophila (97.0%) and Pseudidiomarina salinarum (96.9%). Phylogenomic tree based on UBCG program shows P. halophila as its closest relative. ANI and in-silico DDH with other Pseudidiomarina spp. are lower than 87 and 20%, respectively, suggesting that strain CECT 9734 T represents a new species, for which we propose the name Pseudidiomarina piscicola sp. nov. and CECT 9734 T (= LUBLD50 7a T = LMG 31044 T ) as type strain.

Cellular and Molecular Changes in Hippocampal Glutamate Signaling and Alterations in Learning, Attention, and Impulsivity Following Prenatal Nicotine Exposure - Filip S. Polli; Theis H. Ipsen; Maitane Caballero-Puntiverio; Tina Becher Østerbøg; Susana Aznar; Jesper T. Andreasen; Kristi A. Kohlmeier (Molecular Neurobiology, 2020)

Tamoxifen-independent recombination of reporter genes limits lineage tracing and mosaic analysis using CreERT2 lines - A. Álvarez-Aznar; I. Martínez-Corral; N. Daubel; C. Betsholtz; T. Mäkinen; K. Gaengel (Transgenic Research, 2020)
The CreER T2 /loxP system is widely used to induce conditional gene deletion in mice. One of the main advantages of the system is that Cre-mediated recombination can be controlled in time through Tamoxifen administration. This has allowed researchers to study the function of embryonic lethal genes at later developmental timepoints. In addition, CreER T2 mouse lines are commonly used in combination with reporter genes for lineage tracing and mosaic analysis. In order for these experiments to be reliable, it is crucial that the cell labeling approach only marks the desired cell population and their progeny, as unfaithful expression of reporter genes in other cell types or even unintended labeling of the correct cell population at an undesired time point could lead to wrong conclusions. Here we report that all CreER T2 mouse lines that we have studied exhibit a certain degree of Tamoxifen-independent, basal, Cre activity. Using Ai14 and Ai3, two commonly used fluorescent reporter genes, we show that those basal Cre activity levels are sufficient to label a significant amount of cells in a variety of tissues during embryogenesis, postnatal development and adulthood. This unintended labelling of cells imposes a serious problem for lineage tracing and mosaic analysis experiments. Importantly, however, we find that reporter constructs differ greatly in their susceptibility to basal CreER T2 activity. While Ai14 and Ai3 easily recombine under basal CreER T2 activity levels, mTmG and R26R-EYFP rarely become activated under these conditions and are therefore better suited for cell tracking experiments.

Target of rapamycin signaling is tightly and differently regulated in the plant response under distinct abiotic stresses - Cintia M. Pereyra; Néstor R. Aznar; Marianela S. Rodriguez; Graciela L. Salerno; Giselle M. A. Martínez-Noël (Planta, 2020)

Consumption of pelagic tunicates by cetaceans calves in the Mediterranean Sea - NATALIA FRAIJA-FERNÁNDEZ; ALFONSO A. RAMOS-ESPLÁ; MARÍA ÁNGELES RADUÁN; CARMEN BLANCO; JUAN ANTONIO RAGA; FRANCISCO JAVIER AZNAR (Mediterranean Marine Science, 2018)
Gelatinous zooplankton, including jellyfish, ctenophores and pelagic tunicates, constitutes fragile marine animals that live in the water column, and represent an important resource for marine food webs through their seasonal pulses. Although there is scarce evidence on the occurrence of gelatinous zooplankton in stomach contents of apex, endothermic predators such as cetaceans, the ecological significance of such observations requires consideration. In this study, we report on the occurrence of pelagic tunicates in the stomach of three individual calves of two cetacean species from the western Mediterranean, and collate all previous reports of gelatinous zooplankton in cetacean diets. We then briefly discuss the possible dietary significance of these observations.

Pneumonia in mechanically ventilated patients: no diagnostic and prognostic value of different quantitative tracheal aspirates thresholds - J. Garnacho-Montero; A. Gutiérrez-Pizarraya; I. Lopez-García; J. C. Miranda; V. González-Galán; Y. Corcia-Palomo; I. Alonso-Araujo; L. Martín-Villén; J. Aznar-Martín; R. Amaya-Villar (Infectious Diseases, 2018)

Integrating Science-Based Co-management, Partnerships, Participatory Processes and Stewardship Incentives to Improve the Performance of Small-Scale Fisheries - Kendra A. Karr; Rod Fujita; Ramon Carcamo; Lawrence Epstein; James R. Foley; José A. Fraire-Cervantes; Mauro Gongora; Ollin T. Gonzalez-Cuellar; Pablo Granados-Dieseldorff; Julius Guirjen; Amy H. Weaver; Héctor Licón-González; et al. (Frontiers in Marine Science, 2017)

Tryptophan depletion affects compulsive behaviour in rats: strain dependent effects and associated neuromechanisms - A. Merchán; S. V. Navarro; A. B. Klein; S. Aznar; L. Campa; C. Suñol; M. Moreno; P. Flores (Psychopharmacology, 2017)

Acyl carrier proteins from sunflower (Helianthus annuus L.) seeds and their influence on FatA and FatB acyl-ACP thioesterase activities - Jose A. Aznar-Moreno; Mónica Venegas-Calerón; Enrique Martínez-Force; Rafael Garcés; Joaquín J. Salas (Planta, 2016)

Efficacy of Cinnamaldehyde Against Enteric Viruses and Its Activity After Incorporation Into Biodegradable Multilayer Systems of Interest in Food Packaging - M. J. Fabra; J. L. Castro-Mayorga; W. Randazzo; J. M. Lagarón; A. López-Rubio; R. Aznar; G. Sánchez (Food and Environmental Virology, 2016)

Trunk spines in cystacanths and adults of Corynosoma spp. (Acanthocephala): Corynosoma cetaceum as an exceptional case of phenotypic variability - Francisco J. Aznar; Enrique A. Crespo; Juan A. Raga; Jesús S. Hernández-Orts (Zoomorphology, 2016)

Challenges in the Modeling of Wound Healing Mechanisms in Soft Biological Tissues - C. Valero; E. Javierre; J. M. García-Aznar; A. Menzel; M. J. Gómez-Benito (Annals of Biomedical Engineering, 2015)

Computational Methodology to Determine Fluid Related Parameters of Non Regular Three-Dimensional Scaffolds - Víctor Andrés Acosta Santamaría; M. Malvè; A. Duizabo; A. Mena Tobar; G. Gallego Ferrer; J. M. García Aznar; M. Doblaré; I. Ochoa (Annals of Biomedical Engineering, 2013)

Vertical concentration gradients of volatile organic compounds in two NS-oriented street canyons - Marta Doval Miñarro; Isabel María Morales Terrés; Jose A. Egea; Enrique González Ferradás; Agustín Miñana Aznar (Environmental Monitoring and Assessment, 2012)

Three-Dimensional Simulation of Mandibular Distraction Osteogenesis: Mechanobiological Analysis - E. Reina-Romo; M. J. Gómez-Benito; A. Sampietro-Fuentes; J. Domínguez; J. M. García-Aznar (Annals of Biomedical Engineering, 2011)

Monitoring In Vivo Load Transmission Through an External Fixator - J. Grasa; M. J. Gómez-Benito; L. A. González-Torres; D. Asiaín; F. Quero; J. M. García-Aznar (Annals of Biomedical Engineering, 2010)

Diet of Balaenophilus spp. (Copepoda: Harpacticoida): feeding on keratin at sea? - F. J. Badillo; L. Puig; F. E. Montero; J. A. Raga; F. J. Aznar (Marine Biology, 2007)

Solvent and Temperature Effects on Polymer-Coated Glass Fibers. Fluorescence of the Dansyl Moiety - J. González-Benito; A. Aznar; J. Baselga (Journal of Fluorescence, 2001)

Fluorescence-Labeled Pyrenesulfonamide Response for Characterizing Polymeric Interfaces in Composite Materials - J. González-Benito; A. J. Aznar; J. Lima; F. Bahia; A. L. Maçanita; J. Baselga (Journal of Fluorescence, 2000)

Pyrene-Doped Polyorganosiloxane Layers over Commercial Glass Fibers - J. González-Benito; J. C. Cabanelas; Ma. R. Vigil; A. J. Aznar; J. Bravo; J. Baselga (Journal of Fluorescence, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)